PERUBAHAN MAKNA DALAM NOVEL TENGGELAMNYA KAPAL VAN DER WIJCK KARYA HAMKA - Nani Solihati (FIP Unimed, 2014)
ABSTRACT This study aims to determine the change of meaning in the novel Tenggelamnya Kapal Van Der Wijck by Hamka. The method used is descriptive qualitative method. Source of data in this study is novel Tenggelamnya Kapal Van Der Wijck by Hamka. Based on the results of the analysis conducted , it was found that Hamka in conveying plot, setting, and character using words that are changing the meaning . Change of meaning that occurs is widespread, narrowed, total, refining, and coarsening . Keywords : Change of Meaning, Novel, Hamka